Penerapan Metode Full-Profile Dalam Pengumpulan Data Untuk Analisis Konjoin - Roy Tridoni Situmorang; Desi Yuniarti; Ika Purnamasari (EKSPONENSIAL, 2018)
Conjoint analysis is an analytical technique that is used to examine the impact of attributes of goods or service. Conjoint analysis can be applied to know the attribute that become the main choice of student of Mulawarman University in choosing GSM prepaid card product. Where the attribute used are SMS tariff, phone tariff, internet package, signal and bonuses. The purpose of this study is to know the combination of attribute level which is most interested by student and relative importance value from each attribute. The result of this study is the combination of attributes of the GSM prepaid card that the student are interest in are the SMS package tarif with the utility value is 1,445, the phone tarif per minute with the utility value is 0,525, full 4G internet package with the utility value is 2,51, strong signal with the utility value is 1,895, SMS bonus with the utility value is 1,42. The attribute that become the student’s preferred choice in choosing GSM prepaid card is internet package with the relative importance value is 0,352.